Tuhan, Manusia Dan Eskatologis: Universe, Human, Metaphysics - Nurul Huda (Jurnal Penelitian Multidisiplin, 2022)
The discussion of God, man and eschatology became a central assumption for philosophers.These three elements certainly cannot be separated from human thinking. The concepts built upon each element are so numerous and so vast. It can be seen as the search for knowledge of these three things has been carried out from ancient times to the present. Various polemics are inevitable in talking about this. Accordingly, the author seeks to emphasize the study of God, man and eschatology wrapped up in the environment of the study of religious philosophy. The author formulates a study of how clarity of God is a personal and impersonal substance? What is the clarity of God's absolute dominion and man's freedom? What is the clarity of life after death? The question aims to make it clearer for man to be aware of God, Man and Eschatology in the philosophical environment of religion. In examining this, the author relies on qualitative methods with a